2020
DOI: 10.3354/ame01927
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical fingerprints of marine fungi: implications for trophic and biogeochemical studies

Abstract: Fungi are ubiquitous in the marine environment, but their role in carbon and nitrogen cycling in the ocean, and in particular the quantitative significance of fungal biomass to ocean biogeochemistry, has not yet been assessed. Determination of the biochemical and stable isotope composition of marine fungi can provide a basis for identifying fungal patterns in relation to other microbes and detritus, and thus allow evaluation of their contribution to the transformation of marine organic matter. We characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 129 publications
1
8
0
Order By: Relevance
“…Ergosterol is the most abundant fungal sterol [ 30 ] and it is almost exclusively produced by fungi [ 13 ]. Hence, it has been used to determine fungal biomass in terrestrial and aquatic environments [ 19 ]. However, quantifying ergosterol in open ocean waters and the deep sea requires highly sensitive methods due to the expected low fungal abundance in these environments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ergosterol is the most abundant fungal sterol [ 30 ] and it is almost exclusively produced by fungi [ 13 ]. Hence, it has been used to determine fungal biomass in terrestrial and aquatic environments [ 19 ]. However, quantifying ergosterol in open ocean waters and the deep sea requires highly sensitive methods due to the expected low fungal abundance in these environments.…”
Section: Resultsmentioning
confidence: 99%
“…A property that makes ergosterol especially well-suited as a proxy for fungal biomass is that it contains a 5,7-double bond, which is rare among other sterols [ 9 ]. Additionally, it represents more than 80% of sterols in fungal strains [ 19 ]. Not all fungi are capable to synthesize ergosterol such as many fungi belonging to the division Chytridiomycota [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ergosterol extraction method was recently adapted to marine fungi to allow for the quantification of fungal biomass in the oligotrophic (low productive) regions (Salazar Alekseyeva et al., 2022). However, the ergosterol‐based method falls short when dealing with Chytridiomycota taxa (Gutiérrez et al., 2020), which is important to consider during phytoplankton blooms.…”
Section: Methods For Studying Planktonic Marine Fungimentioning
confidence: 99%
“…There are currently 1,898 described species of marine fungi (https://www.marinefungi.org/, 12 September 2023; Calabon et al., 2023), but their actual diversity is estimated to be much higher, with some studies stating that only around 1% of marine fungi have been identified (Gladfelter et al., 2019; Jones, 2011). In coastal waters, planktonic fungi are commonly found on aggregates or detritus associated (Gutiérrez et al., 2010, 2020). Moreover, they can be associated with other eukaryotes or phytoplankton as pathogens or symbionts (Grossart et al., 2016; Gutiérrez et al., 2010; Raghukumar, 2017a; Richards et al., 2015; Sen et al., 2022).…”
Section: Diversity Of Planktonic Marine Fungimentioning
confidence: 99%
“…Lipids are the main building blocks of microorganisms and occur ubiquitously in the environment. A large number of lipids are synthesized by many different genera and orders of microbes but some lipids are unique to specific organisms or groups of organisms or to specific biogeochemical processes (e.g., Koga et al, 1998;Cvejic et al, 2000;Sinninghe Damsté et al, 2002b;Belt et al, 2007;Rossel et al, 2008;Bauersachs et al, 2009;Elling et al, 2017;Rush and Sinninghe Damsté, 2017;Longo et al, 2018;Gutiérrez et al, 2020), and hence serve as biomarker lipids. Furthermore, intact polar lipids (IPLs) are thought to degrade rapidly upon cell death indicating recent activity of microbial cells (White et al, 1979;Harvey et al, 1986).…”
Section: Introductionmentioning
confidence: 99%